The role of the Internal Audit Charter in Reducing Cases of Financial and Administrative Corruption for Iraqi Economic Units - Laith Jawad Kadhim; Huda Al-Sahrawardee; Wasan Yahia Ahmad (مجلة الغري للعلوم الاقتصادية والادارية)
The phenomenon of corruption is not new, but the volume of corruption that has led many international companies in general and Iraqi economics Units in particular, to the abyss must be taken into account to reduce it. Many international organizations have addressed this phenomenon for instance; (Gray) has defined corruption in general as the abuse of power available to achieve personal returns and profits or to a group of people, who are among them. many Iraqi economics units Suffer from much managerial and financial corruption, because of the weak internal auditing and the weak role of monitoring and control units for the administration's functions. The study offers a proposed model to implement the strategy of description functions. The internal audit charter provides a legal support for the department's work through identifying the objectives of the internal audit function, independence, granted authority and the responsibilities assigned it by determining the scope of work, as well as determining the professional standards followed and types of reports issued by them.In order to impede the fraud and corruption, the study recommends using this charter in order to draw up of strategic and tactical plans to acquire and provide infrastructure, as well as the preparation and evaluation of skills of auditors that help to create an ideal environment which contributes to ending of corruption cases.